Human T-cell Lymphotropic Virus types I and II (HTLV-I/II) in French Guiana: clinical and molecular epidemiology - Mirdad Kazanji; Antoine Gessain
We review here the epidemiological studies performed by our group on human retrovirus HTLV-I and HTLV-II infections and the associated diseases in French Guiana since 1984. French Guiana is an overseas French administrative district located between Brazil and Surinam. Its population is characterized by a large variety of ethnic groups, including several populations of African origin and various populations of Amerindian origin. Several epidemiological studies of large samples of pregnant women and in remote villages showed that HTLV-I is highly endemic in this area but is restricted to groups of African origin, especially the Noir-Marrons. In this endemic population, the results of segregation analysis in a genetic epidemiological study were consistent with the presence of a dominant major gene predisposing to HTLV-I infection, especially in children. In contrast, HTLV-II infection appears to be rare in French Guiana, having been found in only a few individuals of Brazilian origin. From a molecular point of view, the HTLV-I strains present in the Noir-Marrons, Creoles and Amerindians appear to originate from Africa, as they belong to the large cosmopolitan molecular subtype A.